2015
DOI: 10.1515/msp-2015-0098
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced luminescence of rare-earth Tb (III) obtained by mixing of Gd (III) in a fumarate complex and intra-molecular energy transfer

Abstract: Trivalent lanthanide ions display fascinating optical properties. Therefore, the rare-earth complexes of terbium fumarate heptahydrate and GdTb fumarate heptahydrate were grown by using a single gel diffusion technique. The crystals were characterized by different physicochemical techniques of characterization. UV-Vis and photoluminescence spectrophotometric experiments were carried out to study the optical properties of the grown crystals. Under various excitations (339 nm, 350 nm or 368 nm) the terbium fumar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The emission spectra was recorded with excitation at 360 nm (Figure 3IIa), which shows four emission bands at 486, 540, 580, and 620 nm, which is due to the characteristic band of transition 5 D 4 → 7 F J (J=6,5,4,3) for Tb(III). 48,51 Similarly, the emission spectra was recorded in the presence of KBrO 3 as shown in Figure 3IIb. From the spectra, it is seen that the Tb(III) characteristic bands are still present, with no signatures of Tb(IV), indicating that Tb(III) species exist in the presence/absence of KBrO 3 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The emission spectra was recorded with excitation at 360 nm (Figure 3IIa), which shows four emission bands at 486, 540, 580, and 620 nm, which is due to the characteristic band of transition 5 D 4 → 7 F J (J=6,5,4,3) for Tb(III). 48,51 Similarly, the emission spectra was recorded in the presence of KBrO 3 as shown in Figure 3IIb. From the spectra, it is seen that the Tb(III) characteristic bands are still present, with no signatures of Tb(IV), indicating that Tb(III) species exist in the presence/absence of KBrO 3 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In order to enhance the fluorescence properties of the rare-earth complexes, co-luminescence system with two kinds of rare-earth elements has been successfully fabricated. Several authors have also indicated that the addition of the certain second rare-earth ions, such as Gd (III) and La (III), could change the fluorescence properties of the rare-earth complexes [16], for example, SHAH [17] and Zhao [18] found Gd 3+ ions in the mixed complex could remarkably increased the luminescent intensities of the terbium complex; Zhai [19] found the intrinsic fluorescence of Eu 3+ could be enhanced by add Tb 3+ ions and this is primarily due to an energy transfer from the 5 D 4 level of Tb(III) to the 5 D 0 level of Eu(III) ions. The luminescence mechanism is an intra-molecular energy transfer between Gd 3+ and the central Tb 3+ ions and from Tb 3+ to Eu 3+ , that is called "antenna effect".…”
Section: Introductionmentioning
confidence: 99%